2014
DOI: 10.1016/j.ijnt.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of changes in serum phenytoin level after craniotomy and its relation to intra operative blood loss

Abstract: a b s t r a c tProblems considered: Phenytoin is the drug of choice for post operative seizures while some studies have shown lack of efficacy of phenytoin in reducing seizure frequency after craniotomy, which in turn may be due to fall in plasma phenytoin levels after craniotomy. Aims: The aim of the study is to describe changes, if any, in plasma phenytoin levels after craniotomy and its relation to intra operative blood loss. Methods: This was a prospective study in which total of 50 consecutive patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…It is important to note that a sudden drop in perioperative phenytoin levels could potentially increase the risk of postoperative seizures, similar to the abrupt withdrawal of an anticonvulsant drug in a nonsurgical setting. 3,4,27,28 Maintaining a therapeutic level of phenytoin is crucial for effective seizure control, as patients with subtherapeutic levels are more susceptible to seizures. 4,13 The occurrence of postoperative seizures is a complex phenomenon, and subtherapeutic level of phenytoin is one of the contributing Table 4 Comparison of all parameters used in study between two groups, one having seizures and other not having any seizures in their post-operative period Based on this study, it is suggested that a loading dose of 7 to 15 mg/kg may be administered after the closure of dura to prevent a sudden drop in phenytoin levels in the immediate postoperative period, as recommended by other researchers as well.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is important to note that a sudden drop in perioperative phenytoin levels could potentially increase the risk of postoperative seizures, similar to the abrupt withdrawal of an anticonvulsant drug in a nonsurgical setting. 3,4,27,28 Maintaining a therapeutic level of phenytoin is crucial for effective seizure control, as patients with subtherapeutic levels are more susceptible to seizures. 4,13 The occurrence of postoperative seizures is a complex phenomenon, and subtherapeutic level of phenytoin is one of the contributing Table 4 Comparison of all parameters used in study between two groups, one having seizures and other not having any seizures in their post-operative period Based on this study, it is suggested that a loading dose of 7 to 15 mg/kg may be administered after the closure of dura to prevent a sudden drop in phenytoin levels in the immediate postoperative period, as recommended by other researchers as well.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of postcraniotomy seizures varies significantly, ranging from as low as 3% to as high as 92%. [1][2][3][4][5] These variations are closely linked to the specific site of the surgical procedure and the nature of the underlying pathology. Of particular concern is the observation that the greatest risk of seizures is within the initial 48 hours following a surgery.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations